Transparency of the Federal Reserve, a Force of Stability or Volatility in Financial Markets Post 2008 and Prior to COVID-19? - Carolyne C. Soper; Monika K. Sywak (Finanse i Prawo Finansowe)
The purpose of this article is to analyze how the Central Bank of the United States, the Federal Reserve’s decision to provide greater transparency after the Financial Crisis of 2008 impacted the volatility in financial markets. This study uses five Chicago Board Options Exchange Volatility Indices as a proxy for overall market volatility and attempts to capture their deviances from expected returns. The event dates identified are when the United States Federal Reserve met and released their “summary of economic predictions”.